Variety of Current Power Welding Using Electrode 6013 on Tensile Force of Lower Carbon Metal - Bakhori, Ahmad; R. Harahap, Muksin; Napid, Suhardi; Rafiq Yanhar, Muhammad; Hasibuan, Abdurrozzaq (International Journal of Engineering and Technology, 2018)
The objective of this study is to determine the outstanding tensile value on welding of little carbonate steel electrode 6013/ Ө 2.5 x 350 mm in tensile test. Specimen in tested is a lower carbon steel found in market or sometimes available on welding workshops of plate form. This plate is made refer to Standard Tensile Test specimen ASTM E-8M in thick 5 mm and made plot V 450 in twelve pieces. In welding specimen, inflow current varieties with 60, 80, 100, 120 Ampere and constant power of 20 volt and welding position tilted ranges 600 – 700.  In the test found data the lowest tensile strength is 160.62 Mpa of welding current power 60 Ampere and the greatest tensile force 438.80 Mpa with welding power 120 Ampere whereas welding most adaptable is on 80 Ampere 325.96 Mpa. The power force of welding determined to tensile force due electrode fluid completed and influenced to that lower carbon steel mechanical property.